On the connection between the quadratic form and the arithmetic condition in the multi-dimensional limit theorem - Raudeliūnas, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. К. Рауделюнас. О связи квадратичной формы и арифметического условия в многомерной предельной теореме A. Raudeliūnas. Kvadratinės formos ir aritmetinės sąlygos ryšys daugiamatėje ribinėje teoremoje